2021
DOI: 10.1021/acs.chemrestox.0c00367
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-Specific Nitrosamines in the Tobacco and Mainstream Smoke of Commercial Little Cigars

Abstract: Cigars are among the broad variety of tobacco products that have not been as extensively studied and characterized as cigarettes. Small cigars wrapped in a tobacco-containing sheet, commonly referred to as little cigars, are a subcategory that are similar to conventional cigarettes with respect to dimensions, filters, and overall appearance. Tobacco-specific nitrosamines (TSNAs) are carcinogens in the tobacco used in both little cigars and cigarettes. This study uses a validated high-performance liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…Based on these in vitro findings, we concluded that NNK, even at a low dose, can contribute to a dysregulated MMR mechanism and increased cell survival rates, indicating a non-dose-dependent effect of TS-related N -Nitrosamines. We have also recently shown that the combination of N -Nitrosamines, NNK and NDEA, at concentrations based on values previously measured in the mainstream of TS [ 24 , 25 , 26 ] and used in in vivo models [ 6 , 28 , 29 , 30 ], could promote pre-neoplastic lesions in in vivo exposed murine hypopharyngeal mucosa, possibly through the activation of NF- κ B and its related oncogenic pathways [ 6 ]. On the other hand, we have shown that the combination of tobacco smoke N -Nitrosamines with other risk factors, such as bile reflux, was particularly noxious, as it could accelerate the carcinogenic process by causing invasive cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these in vitro findings, we concluded that NNK, even at a low dose, can contribute to a dysregulated MMR mechanism and increased cell survival rates, indicating a non-dose-dependent effect of TS-related N -Nitrosamines. We have also recently shown that the combination of N -Nitrosamines, NNK and NDEA, at concentrations based on values previously measured in the mainstream of TS [ 24 , 25 , 26 ] and used in in vivo models [ 6 , 28 , 29 , 30 ], could promote pre-neoplastic lesions in in vivo exposed murine hypopharyngeal mucosa, possibly through the activation of NF- κ B and its related oncogenic pathways [ 6 ]. On the other hand, we have shown that the combination of tobacco smoke N -Nitrosamines with other risk factors, such as bile reflux, was particularly noxious, as it could accelerate the carcinogenic process by causing invasive cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used an in vivo murine experimental approach involving a long time treatment (14 weeks) of the hypopharynx to TS-related N -Nitrosamines, NNK and NDEA, with or without nicotine, investigating for the first time whether chronic exposure to TS components can affect the MMR mechanism and miRNA markers, previously linked to carcinogenesis of the upper aerodigestive tract [ 19 , 35 , 36 , 41 ]. We used a mixture of NNK and NDEA, with or without nicotine, at concentrations based on our prior in vivo model and other studies [ 6 , 24 , 25 , 26 , 28 , 29 , 30 ]. Our novel in vivo experimental data provides direct evidence that chronic exposure of the murine hypopharyngeal epithelium to TS components can induce a defective MMR mechanism and deregulation of cancer-related regulatory miRNA molecules in premalignant murine HM, providing new insights into the mechanism of TS-related carcinogenesis of the upper aerodigestive tract ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each TCTP type and relevant matrix, each HPHC is in one of three categories: “established data”, “limited data”, and “no data”. An HPHC is categorized as having established data if (1) the literature searches had relevant results and the HPHC did not fall into the limited data category or (2) other ongoing research projects , or subsequent FDA publications from these studies , covered the analysis of this HPHC in a specific tobacco product type and matrix. An HPHC is categorized as having limited data if (1) the publications available did not include domestically available (i.e., United States) commercial TCTP, (2) the publication lacked test method information, (3) the publication methods are outdated (i.e., high detection limit compared to the recent literature), or (4) the publications report conflicting results.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, N accumulates in fresh leaves as nitrates when plants are grown under excess N fertilization [14,16,22,28,29] which, in turn, means a potential high undesirable tobacco specific nitrosamine (TSNA) content in commercial products after the curing period [16,30,31]. TSNAs are potentially carcinogenic compounds [32,33]. Excess N fertilization also decreases the tobacco agronomic N use efficiency, and there is a negative relationship between the percentage amount of N recovered by plants and the increase in the N fertilization rate [14].…”
Section: Introductionmentioning
confidence: 99%